Analisis Struktural Dalam Kajian Al-Qur’an (Surat Yûsuf) - Sembodo Ardi Widodo (Ulumuna, 2007)
Structuralism has its methodological root in the structural linguistics of Ferdinand de Saussure, whose synchronic study of language systems stands in contrast to the diachronic and comparative studies of nineteenth-century philology. One of his contributions is his opinion that language acquires meaning along two axes of relationships: syntagmatic and paradigmatic. As a fundamental thought, the concept has deep influences that were firstly felt by the Russian formalist, then by other structuralists such as Roland Barthes as shown in his structural analysis and Levi-Strauss in his paradigmatic analysis. Levi-Strauss applied his paradigmatic analysis in his two short articles, “The Structural Study of Myth” and “The Story of Asdiwal”. In the first article Strauss presented the complete model of deep-structural analysis to make a brief examination of the Oedipus myth. Based on structural analysis of Levi-Strauss and Roland Barthes, this article tries to analyze the chapter 12 (Yûsuf) of Holy Quran.